Network Analysis of miRNA and mRNA Changes in the Prelimbic Cortex of Rats With Chronic Neuropathic Pain: Pointing to Inflammation - Cai, Guohong; Zhu, Yuanyuan; Zhao, Yan; Chen, Jing; Guo, Chihua; Wu, Feifei; Huang, Jing; Wu, Shengxi (Frontiers in Genetics, 2020)
Neuropathic pain (NP) is a complex, chronic pain condition caused by injury or dysfunction affecting the somatosensory nervous system. This study aimed to identify crucial mRNAs and microRNAs (miRNAs) in the prelimbic cortex (PL) of NP rats. mRNA and miRNA microarrays were applied in the present study. The miRNA-mRNA regulatory network was constructed by using ingenuity pathway analysis (IPA). A total of 35 differentially expressed (DE) RNAs (25 miRNAs and 10 mRNAs) were identified in the spared nerve injury (SNI) group compared with the control group. The DE miRNA-mRNA network showed that IL-6 and tumor necrosis factor (TNF) were core components. Mir-30c-5p and mir-16-5p were the most connected miRNAs in the network. Interestingly, four mRNAs (Rnase 4, Egr2, Rexo4 and Klf2) with significantly increased expression were abundantly expressed in microglia, which was verified by the real-time quantitative polymerase chain reaction (qPCR). Furthermore, Rnase4 and Egr2 expression decreased in M1-polarized macrophages and increased in M2-polarized macrophages. In conclusion, we screened dozens of DE mRNAs and miRNAs in the PL of SNI rats. The core of the DE mRNA and miRNA network pointed to molecules associated with inflammation. Four mRNAs (Rnase4, Egr2, Rexo4 and Klf2) might be the potential markers of M2 polarization.